2016
DOI: 10.1186/s13104-016-2004-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human immunodeficiency virus infection in a cohort of tuberculosis patients at Metema Hospital, Northwest Ethiopia: a 3 years retrospective study

Abstract: BackgroundEthiopia is one of the countries that are highly affected by dual epidemics of human immunodeficiency virus (HIV) and tuberculosis (TB). HIV infection is a known risk factor for the development of active TB and it challenges in diagnosis and treatment of TB. Thus, it is essential to determine the epidemiology of HIV infection among TB patients to guide clinical actions and inform the policy makers. This study was aimed to assess the prevalence of HIV infection among TB patients and to describe the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

20
14
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 15 publications
(11 reference statements)
20
14
2
Order By: Relevance
“…Similarly, the co-infection risk was higher for the same age bracket, which implied that co-infection was more common in the sexually active age group. These findings were contrary to the findings by (32) and (29) who observed that high rates of TB-HIV co-infections were in younger patients (<15 years of age) but consistent to several other studies (30,(33)(34)(35)(36). The study also revealed that a larger proportion of the HIV co-infected cases had extra-pulmonary TB conforming to (37) and (34) who found that the risk of extrapulmonary TB was higher in HIV co-infected cases majorly because of delayed diagnosis especially for the sputum smear-negative…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Similarly, the co-infection risk was higher for the same age bracket, which implied that co-infection was more common in the sexually active age group. These findings were contrary to the findings by (32) and (29) who observed that high rates of TB-HIV co-infections were in younger patients (<15 years of age) but consistent to several other studies (30,(33)(34)(35)(36). The study also revealed that a larger proportion of the HIV co-infected cases had extra-pulmonary TB conforming to (37) and (34) who found that the risk of extrapulmonary TB was higher in HIV co-infected cases majorly because of delayed diagnosis especially for the sputum smear-negative…”
Section: Discussionsupporting
confidence: 69%
“…Ethiopia (30). Globally, Kenya registered 8% TB decline rate per year from 2013 to 2017 amongst other high TB burden countries including the Russian Federation (13%), Ethiopia (12%), Sierra Leone (10%)…”
Section: Discussionmentioning
confidence: 99%
“…This finding was supported by previous studies conducted in Amhara (27.7%) [26], in Ethiopia (29.4%) [27], & in Central Nigeria (36.3%) [28]. However, our findings were higher than studies conducted in the Debre Markos Referral Hospital (16.6%) [13], different studies across Ethiopia (20.3-24.2 %) [14,[29][30][31][32], and a WHO estimation for Ethiopia of 14% (9.6%-19%) [2]. Conversely, the findings were lower than studies conducted in the FelegeHiwot Referral Hospital and Debre Tabor Hospital (41.9%) [20], Zambia (98.3%) [33] & South Africa (>70%) [34].…”
Section: Discussionsupporting
confidence: 89%
“…This nding was supported by previous studies conducted in Amhara (27.7%) [26], Gambella [46], in Ethiopia (29.4%) [27], and in Central Nigeria (36.3%) [28]. However, our ndings were higher than studies conducted in the Debre Markos Referral Hospital (16.6%) [13], different studies across Ethiopia (20.3-24.2 %) [14,[29][30][31][32], and a WHO estimation for Ethiopia of 14% (9.6%-19%) [2]. Conversely, the ndings were lower than studies conducted in the Felege Hiwot Referral Hospital and Debre Tabor Hospital (41.9%) [20], Zambia (98.3%) [33], and South Africa (>70%) [34].…”
Section: Discussionsupporting
confidence: 88%